TOXICITY EVALUATION OF AMMONIUM SULFATE TO ALBINO RAT - T, Siva Kumar; A, Shobha Rani; K, Sujatha; B, Purushotham; P, Neeraja (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: The present study was designed to find out the acute median lethal dose (LD50) of ammonium sulfate (inorganic fertilizer) in Wister albino rats. Methods: A single dose of ammonium sulfate dissolved in distilled water (Milli-Q) and administered intraperitoneally at concentrations of 10, 30, 50,70, 90, 110, 130, and 170 mg/kg body weight, respectively, to experimental animals, and then, they were observed every 3 hrs from prior dose giventime, later 6 hrs, 12 hrs, 24 hrs, to 48 hrs of noticing any abnormal behaviors and toxic signs, symptoms. After 48 hrs, counted the number of rats departed in each group and mortality percentage was calculated. Results: The obtained results were evaluated by the Statistical Probit Analysis Method and 48 hrs LD value for albino rats was found to be 91.5 mg/kg. At a single dose of 10 mg/kg, there is no morality and toxic behaviors were observed. Therefore, this concentration is considered as no observed adverse effect level dose. Conclusion: From the earlier consequences, identification and evaluation of the LD50 50 against ammonium sulfate is crucial for understanding the hyperammonemia because ammonium sulfate has been highly utilized as inorganic fertilizer in agriculture and household gardens. Thus, the knowledge about toxic impacts of ammonia useful for clinical or toxicological approaches; however, the toxicity data are unclear. Hence, the in vitro LD 50 evaluations of target chemical in Wistar rats is highly associated toward in ammonia-related peculiar disorders perceptive and therapy. Keywords: Ammonium sulfate, Fertilizer, Median lethal dose, Mortality, No observed adverse effect level. <!--[endif]--><!--[if !mso]--> <!--[endif]--> 50 <!--[if !mso]--> <!--[endif]--><!--[if !mso & !vml]--> <!--[endif]--><!--[if !vml]--> <!--[if gte vml 1]> <v:shape id="_x0000_s1028" type="#_x0000_t202" style='position:absolute; left:0;text-align:left;margin-left:332.05pt;margin-top:8.35pt;width:5.05pt; height:4.65pt;z-index:-5;mso-position-horizontal-relative:page' filled="f" stroked="f"> <![endif]--><!--[if !vml]--><!--[endif]-->Objective:Thepresentstudywasdesignedtofindouttheacutemedianlethaldose(LD )ofammoniumsulfate(inorganicfertilizer)inWisteralbinorats. <span style="font-size: 8.0pt; font-family: 'Cambria','serif'; mso-fareast-font-family: Cambria; mso-bidi-font-family: Cambria; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US"> Methods:Asingledoseofammoniumsulfatedissolvedindistilledwater(Milli-Q)andadministeredintraperitoneallyatconcentrationsof10,30,50, 70, 90, 110, 130, and 170 mg/kg body weight, respectively, to experimental animals, and then, they were observed every 3 hrs from prior dose given time, later 6 hrs, 12 hrs, 24 hrs, to 48 hrs of noticing any abnormal behaviors and toxic signs, symptoms. After 48 hrs, counted the number of rats departed in each group and mortality percentage was calculated. <span style="font-size: 8.0pt; line-height: 100%; font-family: 'Cambria','serif'; mso-fareast-font-family: Cambria; mso-bidi-font-family: Cambria; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US"> <!--[endif]--><!--[if !mso]--> <!--[endif]--> 50 <!--[if !mso]--> <!--[endif]--><!--[if !mso & !vml]--> <!--[endif]--><!--[if !vml]--> <!--[if gte vml 1]><v:shape id="_x0000_s1030" type="#_x0000_t202" style='position:absolute;left:0;text-align:left; margin-left:416.55pt;margin-top:7pt;width:5.15pt;height:4.65pt;z-index:-3; mso-position-horizontal-relative:page' filled="f" stroked="f"> <![endif]--><!--[if !vml]--><!--[endif]-->Results: The obtained results were evaluated by the Statistical Probit Analysis Method and 48 hrs LD value for albino rats was found to <span style="font-size: 8.0pt; font-family: 'Cambria','serif'; mso-fareast-font-family: Cambria; mso-bidi-font-family: Cambria; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US"> be91.5mg/kg.Atasingledoseof10mg/kg,thereisnomoralityandtoxicbehaviorswereobserved.Therefore,thisconcentrationisconsideredas no observed adverse effect level dose. <span style="font-size: 8.0pt; line-height: 100%; font-family: 'Cambria','serif'; mso-fareast-font-family: Cambria; mso-bidi-font-family: Cambria; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US"> <!--[endif]--><!--[if !mso]--> <!--[endif]--> 50 <!--[if !mso]--> <!--[endif]--><!--[if !mso & !vml]--> <!--[endif]--><!--[if !vml]--> <!--[if gte vml 1]><v:shape id="_x0000_s1031" type="#_x0000_t202" style='position:absolute;left:0;text-align:left; margin-left:337.3pt;margin-top:7pt;width:5.15pt;height:4.65pt;z-index:-2; mso-position-horizontal-relative:page' filled="f" stroked="f"> <![endif]--><!--[if !vml]--><!--[endif]-->Conclusion:Fromtheearlierconsequences,identificationandevaluationoftheLD againstammoniumsulfateiscrucialforunderstandingthe <span style="font-size: 8.0pt; font-family: 'Cambria','serif'; mso-fareast-font-family: Cambria; mso-bidi-font-family: Cambria; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US"> hyperammonemiabecauseammoniumsulfatehasbeenhighlyutilizedasinorganicfertilizerinagricultureandhouseholdgardens.Thus,the knowledgeabouttoxicimpactsofammoniausefulforclinicalortoxicologicalapproaches;however,thetoxicitydataareunclear.Hence,theinvitro <!--[endif]--><!--[if !mso]--> <!--[endif]--> LD <!--[if !mso]--> <!--[endif]--><!--[if !mso & !vml]--> <!--[endif]--><!--[if !vml]--> <!--[if gte vml 1]><v:shape id="_x0000_s1029" type="#_x0000_t202" style='position:absolute;left:0; text-align:left;margin-left:45.65pt;margin-top:1.6pt;width:9.6pt;height:8pt; z-index:-4;mso-position-horizontal-relative:page' filled="f" stroked="f"> <![endif]--><!--[if !vml]--><!--[endif]--><!--[if gte vml 1]><v:shape id="_x0000_s1032" type="#_x0000_t202" style='position:absolute;left:0;text-align:left;margin-left:55.25pt; margin-top:7pt;width:5.15pt;height:4.65pt;z-index:-1; mso-position-horizontal-relative:page' filled="f" stroked="f"> <![endif]--><!--[if !vml]--> <!--[endif]--><!--[if !mso]--> <!--[endif]--> 50 <!--[if !mso]--> <!--[endif]--><!--[if !mso & !vml]--> <!--[endif]--><!--[if !vml]--> <!--[endif]-->evaluations of target chemical in Wistar rats is highly associated toward in ammonia-related peculiar disorders perceptive and therapy. <!--[if gte vml 1]> <![endif]--><!--[if !vml]--> <!--[endif]--><span style="font-size: 8.0pt; font-family: 'Cambria','serif'; mso-fareast-font-family: Cambria; mso-bidi-font-family: Cambria; color: #363435; position: relative; top: .5pt; mso-text-raise: -.5pt; letter-spacing: -.15pt; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">Ke<span style="font-size: 8.0pt; font-family: 'Cambria','serif'; mso-fareast-font-family: Cambria; mso-bidi-font-family: Cambria; color: #363435; position: relative; top: .5pt; mso-text-raise: -.5pt; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">ywords: <span style="font-size: 8.0pt; font-family: 'Cambria','serif'; mso-fareast-font-family: Cambria; mso-bidi-font-family: Cambria; color: #363435; position: relative; top: .5pt; mso-text-raise: -.5pt; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">Ammonium sulfate, Fertilizer, Median lethal dose, Mortality, No observed adverse effect level